Efecto de las condiciones de acondicionamiento y almacenamiento en la calidad y vida útil del arándano (Vaccinium sp.) - Tirado Kulieva, Vicente Amirpasha (2024)
The blueberry (Vaccinium sp.) is considered a good food due to its antioxidant compounds that confer multiple health benefits to the consumer. However, it is susceptible to spoilage, so it is proposed to evaluate the effect of conditioning and storage conditions on the quality and shelf life of blueberries. The method consists of comparing a sample at different temperatures (1 ºC, 13.1 ºC and ambient) and packaging (polyethylene, polypropylene and no packaging), plus an additional experiment to compare the effect of ½ cut on the fruit. The results show that the best storage conditions to maintain blueberry quality according to odor, color, flavor, texture and presence of mold were at 13.1ºC and using polyethylene. The differences were significant (p<0.05) compared to other treatments, extending the shelf life of the fruit up to 21 days. The cut fruit had the shortest shelf life (4 days) due to mechanical damage and exposure to the environment.